2008
DOI: 10.1348/147608308x288780
|View full text |Cite
|
Sign up to set email alerts
|

Building bridges to observational perspectives: A grounded theory of therapy processes in psychosis

Abstract: Building bridges to observational perspectives summarizes the core process in psychological therapy in psychosis. Therapy in psychosis is understood as intimately linking the social and internal world in a dialogical process aimed at enhancing the client's functioning in the social world rather than at specifically developing the private mental experience of reflexivity or mentalizing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 47 publications
(77 reference statements)
1
18
0
1
Order By: Relevance
“…Research suggests that negotiating shared understandings helps to develop new perspectives (Allen et al , ; Dilks et al , ). This study highlighted how important it was for family members to make sense of the development and maintenance of psychosis: it was powerful in shifting attributions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research suggests that negotiating shared understandings helps to develop new perspectives (Allen et al , ; Dilks et al , ). This study highlighted how important it was for family members to make sense of the development and maintenance of psychosis: it was powerful in shifting attributions.…”
Section: Discussionmentioning
confidence: 99%
“…Dilks et al () suggested that the client's interpretation of the difficulties is key. This research also highlights the importance of the family's interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence has highlighted the importance of meaning-making as an important coping strategy with which individuals with psychosis address the significant life disruption that accompanies the onset of their illness. [19][20][21] Moreover, facilitation of meaning-making, including cognitive evaluation of beliefs about one's psychosis, 22 has been hypothesized to be a key psychotherapeutic mechanism through which it can promote positive outcomes among individuals with psychosis. 23 Thus, the same neurological dysfunction that may lead to the experience of distorted auditory perceptions may also contribute to the coping and recovery efforts of individuals with first-episode psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of therapy is to build bridges to a shared understanding and connection to the social world (Dilks, Tasker, & Wren, 2008). The idea of a pregnant therapist raises questions regarding these basic therapeutic assumptions such as how does being pregnant affect the shattered world of the psychotic client and whether by being pregnant the therapist further alienates the client from a shared social world?…”
Section: Psychosis Specific Therapeutic Interventionsmentioning
confidence: 99%